Food Bank Use and Homelessness - Ronald Kneebone; Ali Jadidzadeh (The School of Public Policy Publications)
Problems such as homelessness, food insecurity, and ill health are rarely experienced in isolation from one another. Understanding how they are related is helpful for designing appropriate public policy responses.